1996
DOI: 10.1007/s0021663550332
|View full text |Cite
|
Sign up to set email alerts
|

Thallium and cadmium in recent snow and firn layers in the Canadian Arctic by atomic fluorescence and absorption spectrometries

Abstract: Compared to the Antarctic and Greenland, the Canadian Arctic has seen extremely few trace metal studies on snow and ice. Surface, subsurface and depth samples of snow and firns were collected from the Agassiz Ice Cap, Ellesmere Island, Canada using clean room practices. Results for Tl (directly determined by LEAFS) and Cd (determined by GFAAS) are reported. To our knowledge, the thallium depth profile presented here is the first one so far reported for both polar systems, Greenland or other places. Tl concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Few studies of Tl in the Arctic have been reported (8), although historical records of Tl deposition in central Europe have been developed from peat bogs (9). Tl is highly toxic and listed by the U.S. Environmental Protection Agency as a priority pollutant (5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies of Tl in the Arctic have been reported (8), although historical records of Tl deposition in central Europe have been developed from peat bogs (9). Tl is highly toxic and listed by the U.S. Environmental Protection Agency as a priority pollutant (5).…”
Section: Resultsmentioning
confidence: 99%
“…Heavy metal measurements in polar ice cores are relatively few, and our continuous ACT2 measurements of Pb and Cd are in general agreement with these other measurements. To our knowledge, no measurements of Tl in Arctic ice cores have been published previously, although snow pit samples from the Agassiz Ice Cap in northeastern Canada have been reported (8).…”
Section: Replicate Hr-icp-ms Measurementsmentioning
confidence: 98%
“…However as the total concentration of thallium in aquatic environment is very low an analytical technique featuring high sensitivity and low detection limit is required. Inductively coupled plasma mass spectrometry (ICP-MS) [2][3][4] laser-exited atomic florescence spectrometry (LEAFS) [5] and electhrothermal atomic absorption spectrometry [6][7][8][9][10] (ETAAS) had been used for determination of thallium, but ICP-MS is an expen- * Corresponding author. Tel.…”
Section: Introductionmentioning
confidence: 99%
“…Thallium had been determined by inductively coupled plasma mass spectrometry (ICP-MS) [6][7][8] and laser-excited atomic fluorescence spectrometry (LEAFS). 9 However, ICP-MS is an expensive analytical method and incurs high running cost, and LEAFS is less frequently used. 9 Electrothermal atomic absorption spectrometry (ETAAS) appears to be the method of choice for determination of metal at very low concentration.…”
Section: Introductionmentioning
confidence: 99%
“…9 However, ICP-MS is an expensive analytical method and incurs high running cost, and LEAFS is less frequently used. 9 Electrothermal atomic absorption spectrometry (ETAAS) appears to be the method of choice for determination of metal at very low concentration. 10 This very sensitive and relatively simple method has been used by several workers for determination of thallium.…”
Section: Introductionmentioning
confidence: 99%